WEBSITE-BASED RESEARCH AND COMMUNITY SERVICE INFORMATION SYSTEM USING THE WATERFALL METHOD AT TAKUMI POLYTECHNIC, BEKASI - Nurdin Effendi; Anis Lelitasari; Reza Ilyasa; Rangga Gading Satria; Usman Habib Bahtiar; Wayan Deva Adhisthayana (Elkom: Jurnal Elektronika dan Komputer, 2025)
This study focuses on developing a web-based Research and Community Service Information System (SIPPMAS) for Politeknik Takumi Bekasi, utilizing the Waterfall methodology. The aim is to create an integrated platform that streamlines the management of research and community service activities, from proposal submission and budget allocation to project execution and final reporting. The Waterfall method was chosen for its structured, sequential approach, ensuring a systematic development process through distinct phases: requirements analysis, design, implementation, testing, and maintenance. This approach is expected to enhance data accuracy, improve operational efficiency, and provide real-time project monitoring, ultimately facilitating better collaboration among stakeholders and increasing the overall impact of research and community service initiatives at Politeknik Takumi Bekasi. The system is designed to address current manual administrative challenges, offering a centralized and accessible solution for all users.